Determining which of the classic seven quality tools are in the quality practitioner's RCA tool kit. Issue 1 (31st December 2023) - Barsalou, Matthew
Abstract: The purpose of this study is to determine which of the classic seven quality tools are used by quality professionals during a Root Cause Analysis (RCA). The literature was assessed to determine which quality tools are considered to be part of the seven classic quality tools. The identified tools were then used in a survey of quality professionals in a manufacturing organization, who were asked to select the classic seven quality tools they use during an RCA. An email distribution list was used to send the survey to quality professionals at various locations around the world. The results were then analyzed statistically. The cause and effect diagram was the most commonly used quality tool during an RCA. This was distantly followed by the Pareto chart and then the control chart, followed by the Pareto chart, flow chart, histogram, scatter plot, and run chart. The classic seven quality tools have long been discussed in the literature; however, much of the literature consist of descriptions of their use and not an assessment of which tools are frequently used by quality professionals specifically for RCA. This study identified the seven main classic quality tools used by quality professionals during an RCA.